2009
DOI: 10.1007/s10620-008-0651-x
|View full text |Cite
|
Sign up to set email alerts
|

EUS-Guided Celiac Plexus Neurolysis for Pain due to Chronic Pancreatitis or Pancreatic Cancer Pain: A Meta-Analysis and Systematic Review

Abstract: The objective of this study was to evaluate the efficacy of EUS-guided CPN for pain relief in patients with chronic pancreatitis and pancreatic cancer. An initial search identified 1,439 reference articles, of which 130 relevant articles were selected and reviewed. Data was extracted from 8 studies (N = 283) for EUS-guided CPN for pain due to pancreatic cancer and nine studies for chronic pancreatitis (N = 376) which met the inclusion criteria. With EUS-guided CPN, the pooled proportion of patients with pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(174 citation statements)
references
References 47 publications
3
166
0
5
Order By: Relevance
“…Notably, a large meta-analysis of 8 studies revealed EUS-CPN achieved pain reprieve in 80% of patients, equivocal to standard approaches, with no serious complications. 105 Wyse et al 106 randomized 96 patients with late stage pancreatic adenocarcinoma to early EUS-CPN or standard management. Patients receiving early EUS-CPN reported significant reduction in pain at three months relative to the conventional treatment arm.…”
Section: Eus-guided Anastomosismentioning
confidence: 99%
“…Notably, a large meta-analysis of 8 studies revealed EUS-CPN achieved pain reprieve in 80% of patients, equivocal to standard approaches, with no serious complications. 105 Wyse et al 106 randomized 96 patients with late stage pancreatic adenocarcinoma to early EUS-CPN or standard management. Patients receiving early EUS-CPN reported significant reduction in pain at three months relative to the conventional treatment arm.…”
Section: Eus-guided Anastomosismentioning
confidence: 99%
“…The mean rate of pain alleviation is 72-80%, with a much lower rate of complete pain response [139][140][141]. The post-neurolytic residual pain could be related to non-visceral pain owing to invasion of the muscles or surrounding connective tissue.…”
Section: Pain Palliation By Eus-guided Celiac Plexus Neurolysismentioning
confidence: 99%
“…(Ramesh & Varadarajulu, 2008;Puli et al, 2009;Kaufman et al, 2010) This procedure entails the injection of absolute alcohol under EUS guidance to destroy the sympathetic plexus near the celiac axis. A similar technique involving the injection of triamcinolone is performed in patients with chronic pancreatitis for pain control.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%